An assessment of the pattern of congenital heart disease in children: study in a tertiary care hospital, Rajshahi, Bangladesh - Roy, Kuntal; Shahed, Humayun; Roy, Kaushik; Sarah, Quazi Sahely; Chowdhury, Nandita Sur (International Journal of Contemporary Pediatrics, 2020)
Background: Congenital heart disease is defined as a gross structural abnormality of the heart or intrathoracic great vessels that is actually or potentially of functional significance. The aim of this study was to assess the pattern of congenital heart disease. Methods: It was a hospital based Cross-sectional study carried out prospectively in the department of pediatrics of Rajshahi medical college and hospital from July 2011 to December 2011. The study population was all the children up to 12 years of age admitted in three pediatric units of this hospital during the study period. Results: Among the 147 clinically suspected cases congenital heart disease was confirmed in 110 cases by echocardiography. Thrill was mostly present in 60.5% of VSD cases, in 42.1% of PDA, in 50% of A-V canal defect and 10% of multiple lesions patients. Palpable P2 was present in 27.9% of VSD cases, 15% of TOF, 50% of PS and 30% of multiple lesions patients. Left parasternal heave was found in 25.6% of VSD cases, 15.6% of ASD, 88.2% of TOF, 50% of PS and 40% of multiple lesions patients. Cardiomegaly was present in 5.3% of PDA, 50% of COA, 50% of PS and 20% of multiple lesions cases. Plethoric lung field with cardiomegaly & consolidation was observed in 10% of VSD and 21% of PDA cases. Cardiomegaly with consolidation was observed in 11.6% of VSD & 15.6% of ASD cases. Boot shape heart with oligamic lung was observed in 88.2% of TOF patients. Pulmonary opacity/consolidation was found in 4.7% of VSD cases. Conclusions: It appeared that incidence of CHD is quite significant in RMCH.